The role played by insider transfer information in esports coverage - Rong, Yi; Li, Jiaqi (Frontiers in Sports and Active Living, 2024)
Esports is a rapidly growing industry and related information garners the attention of audiences both inside and outside the arena. The electronic competition system has become more structured over time and there are now standard off-seasons, which coincide tightly with an intensive period of player transfers. However, at the same time, the off-season has few events to cover and transfer information is highly confidential, so any insights regarding possible transfers are of deep interest to audiences. As a result, unofficial esports insiders often leak transfer information. To explore this phenomenon in greater depth, the methodology used in this study was based on the content analysis of information relating to 10-years in the life of the esport Counter-Strike: Global Offensive (CS:GO). Data was collected from the Perfect World Esports APP and the HLTV websites to analyze the informants and the development of transfer information and its influence. It was found that, during the off-season, insider transfer revelations became the primary focus of content in the esports media sector. As the number of viewers participating in discussions about potential transfers has grown, esports tipsters have discovered a new career path within the industry. A comprehensive assessment of the audience and professional practitioners reveals the essential qualities that esports insiders should possess to excel in this field and for their careers to develop.